Assessment Of Roughness Of Machined Surfaces Using Laser - S.Syed Ahamed, Mohamed Yusuff (Universiti Sains Malaysia, 2005)
This report is an assessment approach, which presents the experimental results to measure roughness of machined surface using a laser which is a non-contact method measurement. There are two specimens has been tested which is mild steel and aluminum. Usually, surface roughness is measured in average height of roughness (Ra) and root-mean-square (Rq) for non-contact method measurement. But in non-contact method, the parameters used are average pixels and standard deviation of the profile line. The objectives of this report are to compare the results of the two different methods. Then observing the graph line whether it has some trend or pattern. In order to do this, the contact method is been carry out followed by thee non-contact experiment by using the same specimens. The specimens are machined in some different parameter to see the effect to its surface roughness. This work also presents the use of some programs such as DT-Acquire 2 for image grabbing and Matrox 2.1 which is to do some image processing.